Learning, Evaluation, and Planning (LEAP) Model to Evaluate the WVI’s Economic Development Program in Poso, Central Sulawesi, Indonesia - Budi, K; Setiawati, A; Guntara, D (KnE Social Sciences, 2018)
Conflict in Poso Indonesia, leaving a variety of problems that can happen again at any time. Social issues become important enough to be linked to the development of Indonesia’s vision program to overcome poverty. The welfare gap is a major factor in poverty alleviation, such as increasing income in various sectors. agriculture, services, livestock, and entrepreneurship into the leading sectors. World Vision Indonesia as an organization engaged in social and community empowerment can be a pilot project that works with the government to address various social problems caused by the conflict. Keywords: Community empowerment, capacity building, economic development.